The Impact of Inulin and a Novel Synbiotic (Yeast Saccharomyces cerevisiae Strain 1026 and Inulin) on the Development and Functional State of the Gastrointestinal Canal of Calves - S. Jonova; A. Ilgaza; M. Zolovs (Veterinary Medicine International)
Successful management of the dairy industry is closely related to rearing healthy calves. The proper development of the gastrointestinal canal is crucial to reach this goal. One of the strategies to promote this development is the addition of feed additives to the diet. This research aimed to determine the impact of prebiotic inulin and a new, not commercially available synbiotic (mix of prebiotic inulin and probiotic S. cerevisiae strain 1026) on the development of the gastrointestinal canal of calves by comparing the weight of the stomach, its relative ratio to body weight and evaluating pH, and histological changes in different parts of the gastrointestinal canal and assess whether or not the addition of inulin to the yeast S. cerevisiae improves the abovementioned parameters. We used prebiotic inulin (6 g) and a synbiotic (prebiotic inulin 6 g and probiotic Saccharomyces cerevisiae strain 1026, 5 g). The 56-day long research was conducted with fifteen crossbreed calves (32 ± 6 days old) organized in the control group (CoG), the prebiotic group (PreG), and the synbiotic group (SynG). We determined pH, morphological parameters of different parts of the digestive canal, and morphometric parameters of the stomach. The addition of prebiotic inulin to calves’ diet causes the increase of pH in rumen, abomasum, and intestines but when inulin was added to S. cerevisiae, pH decreased and was even lower than in the control group. Prebiotic inulin and its synbiotic with yeast S. cerevisiae positively impact the development of almost all morphological structures of rumen saccus dorsalis, rumen saccus ventralis, and intestine; moreover, calves from the synbiotic group showed better results in virtually all parameters. However, both inulin and synbiotic did not affect the weight and relative weight of different parts of the stomach. Tested synbiotic has the potential to promote the development of the rumen and other parts of the digestive canal of calves.